Considering the opposite a corrective strategy for social judgement - Lord, Charles G.; Preston, Elizabeth; Lepper, Mark R. (American Psychological Association, 1984)
It is proposed that several biases in social judgment result from a failure to consider possibilities at odds with beliefs and perceptions of the moment. Individuals who are induced to consider the opposite position, therefore, should display less bias in social judgment. In 2 experiments, with 150 undergraduates, this reasoning was applied to 2 domains?biased assimilation of new evidence on social issues and biased hypothesis testing of personality impressions. Ss were induced to consider the opposite through explicit instructions to do so and through stimulus materials that made opposite possibilities more salient. In both experiments, the induction of a consider-the-opposite strategy had greater corrective effect than more demand-laden alternative instructions to be as fair and unbiased as possible. Results are consistent with previous research on perseverance, hindsight, and logical problem solving, and they suggest an effective method of retraining social judgment.